The potential anesthetic threats, challenges and intensive care considerations in patients with HIV infection - Sukhminder Jit Singh Bajwa; Ashish Kulshrestha (Wolters Kluwer Medknow Publications, 2013)
Acquired immunodeficiency syndrome (AIDS) has become a pandemic with ever looming danger of its transmission in health professionals. The number of AIDS patients has increased tremendously over the last two decades, who present for surgical procedures as well as who get admitted in intensive care unit for their critical condition. As such anesthesiologists and intensivists are exposed to potential risk of disease transmission on a daily basis from such patients. The guidelines and protocols formulated in the western world regarding prevention of disease transmission cannot be applied uniformly in the developing nations, such as India due to various factors and limitations. As such there is a continuous need felt in this arena to prevent the catastrophic consequences of AIDS in our medical fraternity while treating such patients in operation theatres and critical care units. This study reviews the various pathophysiological aspects, anesthetic considerations, intensive care implications, and various areas where current knowledge about AIDS can be applied to prevent its potential transmission in high-risk clinical groups.